The Investigation of Eye Tracking Accuracy using Synthetic Images - Ramanauskas, N.; Daunys, G. (Elektronika ir Elektrotechnika, 2003)
Accuracy of videooculography was tested using synthetic eye images. The novel pupil center coordinates extraction method wasproposed. The method exploits averaging of pupil edge coordinates in the same scan line. The novel method accuracy is similar tone ofapproximation by circle method. The proposed method has better computational effectiveness, but is less robust to influence of artifacts.Errors for both methods increase versus noise standard deviation with the same velocity. However the influence of noise is small, ifregion between iris and pupil is sharp. The results of study confirmed that method of videooculography is suitable for recording eyemicromovements. Ill. 6, bibl. 3 (in English, summaries in Lithuanian, English, Russian).